Experimental Study of Runoff and Sediment Yield Affected by Ridge Direction and Width of Sloping Farmland - Liu, Shanshan; Qin, Tianling; Lv, Xizhi; Shi, Xuan; Dong, Biqiong; Wang, Jianwei; Liu, Chun (Frontiers in Earth Science, 2021)
Losses of water and soil from sloping farmlands potentially contribute to water eutrophication and land degradation. However, few studies investigated the combined effects of ridge direction and ridge width on surface runoff and soil losses of sloping farmlands. Nine orthogonal experiments (cross ridge, longitudinal ridge and oblique ridge tillage with 40cm, 60cm and 80cm ridge width) were adopted under natural rainfall conditions for two years in Luanhe river basin of China. Results indicated that ridge direction had significant effects on runoff and sediment yield (P<0.05). The ridge width had no significant effect on runoff and sediment yield. No significant interaction effect was found between ridge direction and width on runoff generation and soil losses of the sloping farmland based on statistical analyses. Compared with cross-ridge tillage (CR) and oblique-ridge tillage (OR), longitudinal-ridge tillage (LR) significantly decreased runoff by 78.9%, 64.9% and soil losses by 88.2% and 83.5%, respectively (P < 0.05). The effects of ridge directions on runoff and sediment yield were related with rainfall intensity. When the rainfall level reached rainstorm, the runoff yield under CR, LR and SR had significant differences (P<0.05). The runoff under LR and OR treatment were 5.16 and 3.3 times of that under CR. When the rainfall level was heavy rain or rainstorm, the sediment yield under LR was significantly greater than that under CR. The sediment yield were 7.32 and 13.45 times of that under CR. Cross ridge-tillage with a ridge width of 40cm is an optimally effective measure for soil and water conservation on sloping farmland in arid and semi-arid regions of China.